1990
DOI: 10.1002/ajp.1350220305
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance and excretion of urinary estrogens and gonadotropins in the female pygmy marmoset (Cebuella pygmaea)

Abstract: By retrospective review of colony records and determinations of urinary hormones we have described the reproductive profile of the female pygmy marmoset (Cebuella pygmaea). The pygmy marmoset is a nonseasonal breeder and gives birth to twins 76% of the time with single births occurring 16% and triplet births 8% of the time. lnterbirth intervals ranged from 149-746 days. First births occurred to females between 24-42 months of age and 5-27 months post pairing. We measured urinary estrone, estradiol and estrone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…Harlow et al, [1983] observed a 27-day cycle that varied by a partner status to a degree of a couple days (single = 28.08, partner = 25.82) in C. jacchus . The nonconceptive ovarian cycle lengths reported for marmosets are similar to nonconceptive ovarian cycle lengths reported for other callithrichids [ S. oedipus , 23.6 d: French et al, 1983; Cebuella , 27.0 d: Ziegler et al, 1990; S. fuscicollis , 25.7 d: Heistermann & Hodges, 1995]. Likewise, the mean gestation length for C. geoffroyi 148.55 ± 1.89 was similar to other Callithrix [ C. kuhlii , 143.1 d: French et al, 1996; C. jacchus , 144.0 d: Hearn; 1983].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Harlow et al, [1983] observed a 27-day cycle that varied by a partner status to a degree of a couple days (single = 28.08, partner = 25.82) in C. jacchus . The nonconceptive ovarian cycle lengths reported for marmosets are similar to nonconceptive ovarian cycle lengths reported for other callithrichids [ S. oedipus , 23.6 d: French et al, 1983; Cebuella , 27.0 d: Ziegler et al, 1990; S. fuscicollis , 25.7 d: Heistermann & Hodges, 1995]. Likewise, the mean gestation length for C. geoffroyi 148.55 ± 1.89 was similar to other Callithrix [ C. kuhlii , 143.1 d: French et al, 1996; C. jacchus , 144.0 d: Hearn; 1983].…”
Section: Discussionsupporting
confidence: 80%
“…These include Saguinus [Brand, 1981; French et al, 1983; Heistermann et al, 1993; Heistermann & Hodges, 1995; Lottker et al, 2004, Ziegler et al, 1987], Cebuella [Ziegler et al, 1990], Leontopithecus [French & Stribley, 1985,1987; French et al,1992], and Callithrix [Eastman et al, 1984; French et al, 1996; Harding et al, 1982; Harlow et al, 1983; Hearn & Chambers, 1980; Heger & Neubert, 1987; Hodges & Eastman, 1984; Gilchrist et al, 2001; Tardif et al, 2003]. However, this information is limited, as these data are available for only a small number of species.…”
Section: Introductionmentioning
confidence: 99%
“…The profile of urinary excretion of oestrone-3-conjugates closely reflects that of oestrone-3-conjugates in the circulation, supporting the conclusions of previous studies based on urinary hormones only, that urinary oestrone-3-conjugates are high during the luteal phase (Ziegler et al, 1989(Ziegler et al, , 1990aCarroll et al, 1990). Furthermore, studies based on the profiles of reproductive peptides and steroids in the urine of the cotton-top tamarin (Ziegler et al, 1987), golden-lion tamarin (French et al, 1992) and pygmy marmoset (Ziegler et al, 1990b), also strongly suggest that oestrogen excretion is high in the luteal phase relative to the follicular phase in clawed New World monkeys. Whereas Carroll et al (1990) …”
Section: Methodssupporting
confidence: 80%
“…Gestation length in Cebuella (142 days: Ziegler et al, 1990a) is more similar to those in Callithrix than in either Saguinus or Leontop- ithecus (although a recent report [Heistermann and Hodges, 19951 with endocrinebased estimates of gestation length in three pregnancies in s. fuscicollis yielded a value similar to that for marmosets, 149.7 days). In all females who were actively breeding, there was an immediate postpartum ovulation within 2 weeks of delivering offspring (mean = 13.6 days).…”
Section: Discussionmentioning
confidence: 85%
“…Information on normative reproductive parameters is now available for at least one representative of each of the four genera of callitrichid primates (or five, depending on whether Callimico is included in the list). This includes Saguinus (Brand, 1981;French et al, 1983;Ziegler et al, 1987;Epple & Katz, 1984;Heistermann and Hodges, 1995), Cebuella (Ziegler et al, 1990a), Leontopithecus (French & Stribley, 1985French et al, 1992), Callithrix (Eastman et al, 1984;Hodges & Eastman, 1984;Heger & Neubert, 19871, and Callimico (Carroll et al, 1990;Ziegler et al, 1990a;Pryce et al, 1993b). For each genus, however, information is limited to one or two species.…”
Section: Introductionmentioning
confidence: 99%